الرسم الكاريكاتيري واثره في تعلم الرسم التعبيري: وحدات تعليمية - البياتي، نجم عبدالله عسكر; البكري، سامر عوني رزوقي (الجامعة المستنصرية - كلية التربية الأساسية, 2015)
يعد الرسم الكاريكاتيري أحد مجالات الفنون التشكيلية التي لم يتم تناولها أو الولوج إلى تفاصيلها أو استثمارها في مجال تعليم الفنون بالمستوى الجامعي، وقد ارتأى الباحثان القيام بهذه الخطوة المهمة في جانب من جوانب الرسم التعبيري وذلك بتنظيم مادة تعليمية للرسم الكاريكاتيري وفقاً لخطة (كيلر) النصية والتي تعد واحدة من طرق تفريد التعليم والي قد يتناسب مع تعلم مهارة الرسم بما يشجع الطالب على التعلم بنفسه فضلا عن ما يولده لديه الاندفاع والمنافسة مع بقية أقرانه. حيث هدف البحث الحالي إعداد وحدات تعلمية -تعليمية في فن رسم الكاريكاتير لطلبة قسم التربية الفنية ومن ثم العمل على معرفة دور فن الرسم الكاريكاتيري في تنمية الرسم التعبيري لدى الطلبة ولتحقيق هذا الهدف تم اختبار الفرضية الآتية: ((لا توجد فروق ذات دلالة إحصائية عند مستوى (0.05) بين متوسط درجات طلبة المجموعة التجريبية في رسوماتهم التعبيرية في الاختبار التحصيل القبلي وبين متوسط درجاتهم في الاختبار البعدي)). تكون مجتمع البحث من طلبة قسم التربية الفنية -كلية التربية الأساسية / جامعة ديالى الصف الثالث قاعة (1) في كلية التربية الأساسية / الجامعة المستنصرية عينة التجربة الاستطلاعية وقد بلغ عددهم بالمحصلة النهائية (10) طلبة، تم اختيار عينة البحث من طلبة الصف الثالث والبالغ عددهم (33) طالبا وطالبة بالطريقة القصدية من طلبة جامعة ديالى للعام الدراسي 2004/2005 تم استبعاد (20) منهم لعدم الالتزام بالحضور، وبذلك أصبح العدد (13) طالباً وطالبة وكانت أداة البحث اختبارا محكي المرجع. أما الوسائل الإحصائية التي استخدمت فهي الاختبار التائي لوسطين مرتبطين ومعامل ارتباط بيرسون لإيجاد معامل الارتباط ومعادلة سبيرمان -براون لإيجاد. معامل الثبات. ومن أهم نتائج البحث تفوق عينة البحث التجريبية في الاختبار البعدي الذي تم بعد تطبيق الوحدات التعليمية في فن الرسم الكاريكاتيري عليهم قياساً مع الاختبار القبلي، وكان الفرق دالا إحصائيا وبذلك رفضت الفرضية الصفرية.
The art of caricature drawing is one of the categories of plastic arts which has never been discussed, dealt with its perspectives or made use of its relationship in the field of art education. The researcher thought to take this step forward by organizing the subject modules of caricature drawing according to Keller Plan. This plan is one of the individualized teaching methods, which fits to the process of learning the skill of caricature drawing. In addition, this plan encourages the students to learn and acquire by him/her self and ultimately generating an intense interest and competition inside themselves with other students. This paper aims at composing the teaching/ learning units in the art of caricature drawing for students of the departments of art education. It is to identify the effect of caricature drawing on students' achievement. In order to achieve the above mentioned goals, the researcher tested the following hypothesis:- There are not statistically significant differences at (0,05) level between the mean scores in pre- and post-test scores of the experimental group students of caricature subject. The research population was constituted by students of departments of art education of the College of Basic Education of Diyala University and Al-Mustansiriya University. The students of art education, for example ( 3rd grade - class 1) in the College of Basic Education of Al-Mustansiriya University constituted the sample of exploratory experiment and they were just (10) students. The research sample was of (33) male and female students and they were selected intentionally from 3rd grade students of Diyala University for the academic year of 2004-2005 , though (20) students were excluded for not being attended to the test, therefore the test included just 13 male and female students by using a Criterion-Referenced Test as a research instrument. The statistical means used by researcher are T test for two associated means and Pearson Correlation Coefficient to identify the correlation coefficient and Spearman-Brown prophecy formula. The results demonstrated that experimental group sample of students has surpassed in post test, which was achieved after applying the instructional design on students, in comparison with pretest, therefore the difference was statistically significant and as a result the null hypothesis has been rejected.
Keywords: الفنون التشكيلية -- الرسم الكاريكاتيري -- طلاب التربية الفنية -- الفنون التعبيرية